The healing power of mind : simple meditation exercises for health, well-being, and enlightenment - Tulku Thondup (Boston : Colorado : Shambhala, 1998)
The true nature of our minds is enlightened and peaceful, as the depth of the ocean is calm and clear. But when we mentally grasp and emotionally cling to our wants and worries with all our energy, we lose our own enlightened freedom and healing power, only to gain stress and exhaustion, suffering and overexcitement, like the turbulent waves rolling on the surface of the ocean. Our minds possess the power to heal pain and stress, and to blossom into peace and joy, by loosening the clinging attitudes that Buddhists call " grasping at self.&Quot; if we apply the Mind's healing power, we can heal not only our mental and emotional afflictions, but physical problems also. This book is an invitation to awaken the healing power of mind through inspiring images and sounds, mindful movements, positive perceptions, soothing feelings, trusting confidence, and the realisation of openness. The healing principle on which these exercises are based is the universal nature and omnipresent power envisioned in Mahayana Buddhism. Yet for healing, we don't have to be believers in any particular faith. We can heal body and mind simply by being what we truly are, and by allowing our own natural healing qualities to manifest: a peaceful and open mind, a loving and positive attitude, and warm, joyful energy in a state of balance and harmony.
included bibliographical and glosssary
Keywords: Spiritual life -- Buddhism; Health -- Buddhism; Spiritual healing